The Concept of Environmental Conservation in the Teachings of Saint Jambheshwar: An Overview: संत जाम्भेश्वर की शिक्षाओं में निहित पर्यावरण संरक्षण की अवधारणा: एक अवलोकन - Kumar, Arvind (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Saint Jambheshwar was a great social reformer and environmental thinker within the Indian saint tradition who conveyed the message of establishing harmony among human beings, society, and nature through his life and teachings. He did not limit environmental conservation merely to the protection of natural resources; rather, he presented it as a religious, moral, and social duty. In the 29 principles propounded by him, a deep awareness regarding the protection of trees, water sources, wildlife, biodiversity, and a clean and disciplined lifestyle is clearly evident. These principles not only guide spiritual and religious discipline but also suggest practical and ethical measures to maintain balance between humans and nature. This research paper analyzes the concept of environmental conservation embedded in the teachings of Saint Jambheshwar and examines the relevance of his perspective in the context of growing environmental problems in the modern era, such as deforestation, water and air pollution, loss of biodiversity, and the adverse effects of consumerism. The study makes it clear that the philosophy of Saint Jambheshwar aligns closely with contemporary ideas of sustainable development, environmental ethics, and social responsibility. His teachings continue to inspire human society to adopt compassion, restraint, and responsibility toward nature. Abstract in Hindi Language: संत जाम्भेश्वर भारतीय संत परंपरा के एक महान समाज-सुधारक और पर्यावरण चिंतक थे, जिन्होंने अपने जीवन और शिक्षाओं के माध्यम से मानव, समाज और प्रकृति के बीच संतुलन स्थापित करने का संदेश दिया। उन्होंने पर्यावरण संरक्षण को केवल प्राकृतिक संसाधनों की सुरक्षा तक सीमित नहीं रखा, बल्कि इसे धार्मिक, नैतिक और सामाजिक कर्तव्य के रूप में प्रस्तुत किया। उनके द्वारा प्रतिपादित 29 नियमों में वृक्षों, जल स्रोतों, वन्यजीवों, जैव विविधता और स्वच्छ जीवन शैली के संरक्षण की गहन चेतना स्पष्ट रूप से दिखाई देती है। ये नियम न केवल आध्यात्मिक और धार्मिक अनुशासन का मार्गदर्शन करते हैं, बल्कि मानव और प्रकृति के बीच संतुलन बनाए रखने के व्यावहारिक और नैतिक उपाय भी सुझाते हैं। यह शोध-पत्र संत जाम्भेश्वर की शिक्षाओं में निहित पर्यावरण संरक्षण की अवधारणा का विश्लेषण प्रस्तुत करता है और आधुनिक युग में बढ़ती पर्यावरणीय समस्याओं, जैसे वनों की कटाई, जल और वायु प्रदूषण, जैव विविधता का क्षरण तथा उपभोक्तावाद के दुष्परिणाम, के संदर्भ में उनके दृष्टिकोण की प्रासंगिकता का अवलोकन करता है। अध्ययन से यह स्पष्ट होता है कि संत जाम्भेश्वर का दर्शन आज के सतत विकास, पर्यावरणीय नैतिकता और सामाजिक जिम्मेदारी की अवधारणाओं से पूरी तरह सामंजस्य रखता है। उनकी शिक्षाएँ आज भी मानव समाज को प्रकृति के प्रति करुणा, संयम और उत्तरदायित्व अपनाने के लिए प्रेरित करती हैं। Keywords: संत जाम्भेश्वर, पर्यावरण संरक्षण, बिश्नोई संप्रदाय, 29 नियम, पर्यावरणीय नैतिकता, सतत विकास।